Sexual offender research and treatment in the Netherlands - Frenken, Jos (Journal of interpersonal violence, 1999)
The number of men in the Netherlands who were convicted of sexual offenses rose significantly between 1980 and 1994. Empirical studies of offenders are relatively scarce, although interest in the field is growing. Since the late 1980s, the number of outpatient treatment facilities for these men has increased-especially now that some child molesters are given a choice by the courts between treatment and prison sentence. Since the 1930s, sexual offenders with severe personality disorders that are held not responsible for their offenses are court-ordered to be treated in maximum security forensic psychiatric clinics. Until the mid-1980s, the treatment model for these offenders was based on a derivation of psychoanalytic and Rogerian therapy aimed at personality reconstruction. Since the 1990s, however, the focus has been on the behavior itself, and directive cognitive behavioral elements are now included in the eclectic treatment in several clinics